2021
DOI: 10.1007/s10552-021-01460-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining the etiology of early-onset breast cancer in the Canadian Partnership for Tomorrow’s Health (CanPath)

Abstract: Purpose: Breast cancer incidence among younger women (under age 50) has increased over the past 25 years, yet little is known about the etiology among this age group. The objective of this study was to investigate relationships between modi able and non-modi able risk factors and early-onset breast cancer among three prospective Canadian cohorts.Methods: A matched case-control study was conducted using data from Alberta's Tomorrow Project, BC Generations Project, and the Ontario Health Study. Participants diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
3
1
Order By: Relevance
“…According to menopausal status, our findings indicate that high WC and WHR promote BC in young women, both premenopausal and postmenopausal. Regarding premenopausal status, the finding is consistent with other prospective studies that have adjusted for BMI in premenopausal women (52,57,59,62,67,76). The mechanisms underlying the increased central obesity and BC risk differ between premenopausal and postmenopausal.…”
Section: Erence In Menstrual Statussupporting
confidence: 90%
“…According to menopausal status, our findings indicate that high WC and WHR promote BC in young women, both premenopausal and postmenopausal. Regarding premenopausal status, the finding is consistent with other prospective studies that have adjusted for BMI in premenopausal women (52,57,59,62,67,76). The mechanisms underlying the increased central obesity and BC risk differ between premenopausal and postmenopausal.…”
Section: Erence In Menstrual Statussupporting
confidence: 90%
“…In the case of normal weight or overweight (though not morbidly obese) female subjects, our study found that up to 16% had been smokers at some time during their lives. This percentage was lower than in other studies, such as the one carried out by Pader et al (2021), in which the percentage of past smokers was 27%. These differences could stem from a greater awareness of the adverse effects of cigarette consumption for women suffering from cancer.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, the risk of developing cancer is high in the case of obese female smokers, especially those who began smoking at a young age, and who have continued smoking over a long period of time (Byrne et al, 2010; Pader et al, 2021; Reynolds, 2013; van Kruijsdijk et al, 2013). Luo et al (2011) studied a sample population of 79,990 women, 50 to 79 years of age, and found that obese post-menopausal women who were active smokers were at greater risk of developing breast cancer than non-obese post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…While we have shown that OTTEHR enables knowledge transfer between datasets, it would be interesting to further evaluate OTTEHR on other relevant regression and classification tasks and other demographic factors. These include predicting the time interval between consecutive visits [Poole et al, 2016] and mortality rates [Goodacre et al, 2006], using appropriate and potentially larger datasets [Pader et al, 2021, Sudlow et al, 2015]. Also, extending our method to semi-supervised transfer learning [Wei et al, 2019] and designing a unified model that simultaneously solves feature embedding and classification problems [Song et al, 2017] could improve predictive performance on target domains with limited labeled data.…”
Section: Discussionmentioning
confidence: 99%